Administrators Roles in Enhancing Performance of Facilitators in Open and Distance Learning Study Centers in Rivers State - U, Osuji, Catherine; Omenogo, Anyanwu, Dorathy (MultiTech Publisher, 2024)
The study aimed to understand the role of administrators in enhancing the performance of facilitators in open and distance learning centers in Rivers State. The study involved 73 facilitators, 41 males and 32 females, from study centers in Port Harcourt and Iriebe. A structured questionnaire was used, validated by experts in Measurement and Evaluation and the Department of Educational Management at Rivers State University. Key findings revealed that facilitators lack proficiency in using information and communication tools, irregular allowances undermine motivation, and inadequate facilities do not align with the increasing student population. The study recommends effective collaboration between administrators and facilitators to improve facilitator performance.